(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the substantial components of the concept of «Tree». Universal, nationalcultural and individual layers are identified. It holds indetail description of the «layer» of the concept of «Tree». As the material of description the works of the famous contemporary writer B. Kanapianov were considered. The researcher highlights language means that represent the concept of «Tree». The focusing on the context of language units representing the concept of «Tree» gives an opportunity to reveal the periphery of the concept, to describe the meaning shades that are not fixed in any lexicographical sources, and finally to discover the peculiarities of studied concept in linguocultural aspect. The technique of the conceptual analysis presented in the article can be used at research of language of any work of art.